PROAKFIT: Aplikasi Pengelolaan Proyek Akhir Fakultas Ilmu Terapan - Bagas Saputro, Dimas; Indah Mega Mandasari, Rizza (eProceedings of Applied Science, 2023)
The final project is one of the requirements for graduating students at the Telkom university's applied sciences. The final project is a scientific work constructed on the basis of a carefully executed problem. Students may graduate when they have completed the final project and have also passed the congregation. There were some processes that had to be done to attend the final project congregation. These are the congregation registration, the administration of the congregation, and the revision of the congregation. At the process of enrolment the student council must request an immediate signature from the guardian teacher, this was because it took a long time. Then at the collecting of the student files at the registration, LAK needs a student file at least 11 documents collected for the verification process of a congregation registration. From the problem described, an application could solve the problem. This application was built on a web platform that uses the MySQL database and the framework Laravel.Keywords— Final Project, congregation, applied sciences, MySQL, Laravel, web.